Does the Long-Run Ppp Hypothesis Hold for Africa? : Evidence From Panel Co-Integration Study - Nagayasu, Jun (IMF Working Papers; Working Paper, 1998)
This paper addresses whether parallel market exchange rates in Africa behave in the long run in a manner consistent with the purchasing power parity (PPP) hypothesis. A recent econometric method, the panel co-integration test, enables us to examine the long-run PPP hypothesis by pooling the time-series data of several countries. This approach is particularly useful when analyzing African countries, which often do not have long time series. Using pooled data for 16 African countries, the study concludes that the behavior of parallel market exchange rates in Africa is consistent with the long-run PPP hypothesis.